The FGF and FGFR Gene Family and Risk of Cleft Lip with or Without Cleft Palate. (January 2013) - Wang, Hong; Zhang, Tianxiao; Wu, Tao; Hetmanski, Jacqueline B.; Ruczinski, Ingo; Schwender, Holger; Yee Liang, Kung; Murray, Tanda; Daniele Fallin, M.; Redett, Richard J.; Raymond, Gerald V.; Jin, Sheng-Chih; et al.
Background: Isolated, nonsyndromic cleft lip with or without cleft palate is a common human congenital malformation with a complex and heterogeneous etiology. Genes coding for fibroblast growth factors and their receptors ( FGF/FGFR genes) are excellent candidate genes. Methods: We tested single-nucleotide polymorphic markers in 10 FGF/FGFR genes (including FGFBP1, FGF2, FGF10, FGF18, FGFR1, FGFR2, FGF19, FGF4, FGF3, and FGF9) for genotypic effects, interactions with one another, and with common maternal environmental exposures in 221 Asian and 76 Maryland case-parent trios ascertained through a child with isolated, nonsyndromic cleft lip with or without cleft palate. Results: Both FGFR1 and FGF19 yielded evidence of linkage and association in the transmission disequilibrium test, confirming previous evidence. Haplotypes of three single-nucleotide polymorphisms in FGFR1 were nominally significant among Asian trios. Estimated odds ratios for individual single-nucleotide polymorphic markers and haplotypes of multiple markers in FGF19 ranged from 1.31 to 1.87. We also found suggestive evidence of maternal genotypic effects for markers in FGF2 and FGF10 among Asian trios. Tests for gene-environment (G x E) interaction between markers in FGFR2 and maternal smoking or multivitamin supplementation yielded significant evidence of G x E interaction separately. Tests of gene-gene (G x G) interaction using Cordell's method yielded significant evidence between single-nucleotide polymorphisms in FGF9 and FGF18, which was confirmed in an independent sample of trios from an international consortium. Conclusion: Our results suggest several genes in the FGF/FGFR family may influence risk for isolated, nonsyndromic cleft lip with or without cleft palate through distinct biological mechanisms.